(untitled) (Jurnal Ekonomi dan Manajemen, 2024)
This study aims to determine the perception of batik on the benefits of batik competency certification in Malang Raya, East Java. Competency certification is considered an effort to improve the quality of human resources (HR) in the batik industry, especially in the face of global competition and economic challenges after the Covid-19 pandemic. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews with three batik makers who have taken the competency test. The data was analyzed using triangulation techniques to ensure the validity and reliability of the research results. The results of the study show that batik has a diverse perception of competency certification. Most batik makers see certification as a tool to increase credibility and competitiveness, although some consider it only a formality. Batik also realizes the importance of certification in improving the quality of batik production and marketing. However, there is still ignorance about the differences in certifications issued by various institutions and the long-term benefits of such certifications. Competency certification has the potential to improve the quality and competitiveness of batik, but more intensive socialization is needed regarding the benefits and certification procedures so that batik can utilize it optimally.